HUBUNGAN PENGAWASAN DENGAN PERILAKU AMAN BURUH BANGUNAN DI KABUPATEN BADUNG TAHUN 2019 - Supardi, Kezia Leditia; Muliawan, Partha (ARCHIVE OF COMMUNITY HEALTH; Vol 6 No 2 (2019): Desember 2019DO - 10.24843/ACH.2019.v06.i02.p05, 2019)
ABSTRACT Supervision is an important factor that reinforces the emergence of a person's behavior at workplace. The purpose of this study is to know  the relationship between supervision of occupational health and safety (OHS) and safe behavior in preventing work accidents. This study uses a quantitative method with analytical crossectional approach to determine the relationship of supervision with safety behavior. The subjects of this study were 213 workers selected by systematic random sampling method.  The result show 55,87% has unsafe behavior. There is a relationship between OHS supervision (OR = 3.21; 95% CI = 1,809-5,681; p = 0,000) and occupational safety knowledge (OR = 1.88; 95% CI = 1,049-3,368; p = 0.034). The most significant factor influencing safety behavior is OSH supervision. In addition, respondents who have a good perception of OHS supervision 3.2 times will behave more safely than respondents who have a poor perception of OHS supervision. Suggestion for workers are to always obey the rules set by the company and for supervisors to increase supervision of workerss and conduct monitoring and evaluation of  worker’s safety behavior. Key Words : Safe Behavior, Supervision, Construction